Preparation method and device of controllable structure copper-based compound super-hydrophilic material
Patent Information
- Application Number
- CN202211179737.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-27
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-09-27
AI Technical Summary
[0004]基于此,有必要针对在复杂结构铜基材料表面制备的氢氧化铜纳米材料或纳米花状氧化铜的分布不均匀的问题,提供一种可控结构铜基化合物超亲水材料的制备方法,该方法通过循环反应的方式在铜基材料表面原位生长制备纳米线状氢氧化铜或纳米花状氧化铜,具有操作简单、重复性好、成本低且适合处理不同结构的铜基材料的特点
[0045](1) This invention develops a strong base oxidation method for preparing copper hydroxide with nanowire-like or nanoflower-like structures. This method is simple, easy to operate, and has a short processing time. It can be applied to the processing of copper-based materials with complex geometric structures.
Smart Images

Figure CN117821958B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional materials preparation technology, and in particular to a method for preparing copper-based materials with complex structures by in-situ growing nanowire-like copper hydroxide or nanoflower-like copper oxide. Furthermore, by changing the synthesis conditions, a variety of copper-based compound superhydrophilic materials with controllable structures can be prepared. Background Technology
[0002] Copper hydroxide (COH) is an important industrial material due to its environmental friendliness and low cost, and can be used in pharmaceuticals, pesticides, mordants, pigments, and catalysts. COH is a layered material with an orthorhombic crystal system, space group Cmc21, and a ferrihydrite γ-FeOOH crystal form. Each unit cell contains four COH units, and it is often used to fabricate one-dimensional micro / nanostructures. Copper or copper alloys can be processed to create a COH layer on their surface for surface modification, enabling applications in various fields. For example, this method can be applied to water distillation, where a superhydrophilic COH coating on the packing material increases the strength of the gas-liquid interface and enhances heterogeneous mass transfer processes. COH is also a ferroelectric material with superconducting properties, and can be used to fabricate supercapacitors and sensors.
[0003] To date, researchers have employed various methods to prepare a variety of one-dimensional nanomaterials, including copper hydroxide nanoribbons, nanopillars, nanowires, and nanoneedles. Each method has its advantages and disadvantages. The hydrothermal method for preparing copper hydroxide is relatively complex, requiring copper acetate and ammonia as precursors, which are dehydrated at 180°C to form needle-like copper hydroxide. This process is time-consuming and energy-intensive. The electrolytic method requires adding a copper hydroxide collector to the electrolyte solution and then filtering to obtain copper hydroxide. This process is cumbersome, and the proportions of the added reagents are not precise enough, easily leading to waste. Immersing copper-based materials in a mixture of ammonium persulfate and sodium hydroxide can prepare copper hydroxide with various structures on the surface of copper-based materials. This method is simple and energy-efficient; however, when processing complex copper materials, the non-uniform spatial distribution of the copper material leads to an uneven structural distribution of the resulting copper hydroxide. Summary of the Invention
[0004] Therefore, it is necessary to provide a method for preparing superhydrophilic copper-based compound materials with controllable structure to address the problem of uneven distribution of copper hydroxide nanomaterials or nanoflower-like copper oxides prepared on the surface of complex copper-based materials. This method prepares nanowire-like copper hydroxide or nanoflower-like copper oxides in situ on the surface of copper-based materials through a cyclic reaction. It has the advantages of simple operation, good repeatability, low cost, and suitability for processing copper-based materials with different structures.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for preparing a controllable structured copper-based compound superhydrophilic material includes the following steps:
[0007] (1) A mixed solution of strong alkali and persulfate is passed through copper or copper alloy material to react. The reaction solution that flows out is then returned to flow through copper or copper alloy material again to carry out a cyclic reaction.
[0008] (2) When the reaction solution flowing out in step (1) changes from a colorless solution to a light gray transparent solution, add a fresh mixture of strong base and persulfate to the reaction solution, and then carry out the cyclic reaction.
[0009] (3) Repeat step (2) 1 to 3 times;
[0010] (4) When the reaction solution flowing out in step (3) becomes a light gray transparent solution, the obtained copper or copper alloy material is cleaned and dried to obtain a controllable structure copper-based compound superhydrophilic material with a nanowire copper hydroxide or nanoflower copper oxide structure on the surface.
[0011] Furthermore, the copper or copper alloy material has a copper purity of 95-99.99%, and uses materials such as bulk packing or structured packing of different sizes commonly used in industry. For example, the bulk packing can be at least one of the following: Sita rings, Pall rings, Raschig rings, rectangular saddle rings, and stepped rings; the structured packing can be at least one of the following: wire mesh corrugated packing, perforated plate corrugated packing, plate mesh corrugated packing, and perforated plate corrugated packing.
[0012] Furthermore, the strong alkali is at least one of the common alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide; the persulfate is at least one of the common ammonium persulfate, sodium persulfate, and potassium persulfate.
[0013] Furthermore, the concentration of the strong base is 0.5–3.0 mol·L⁻¹. -1 The concentration of persulfate is 0.025–0.15 mol·L⁻¹. -1 Preferably, the molar ratio of the strong base to the persulfate in the mixed solution is (12-60):1, more preferably (15-25):1. The fresh mixed solution of the strong base and persulfate has the same composition as the initial mixed solution of the strong base and persulfate.
[0014] Furthermore, the ratio of the molar amount of copper in the copper or copper alloy material to the molar amount of persulfate in the original mixed solution is 80 to 300.
[0015] Furthermore, in steps (1) to (3), the reactions are all carried out at 5 to 60°C.
[0016] Furthermore, the flow rate of the mixed solution or reaction solution is controlled to be 0.001–0.1 m·s. -1 When the flow rate is controlled at 0.001–0.02 m·s, a nanowire-like copper hydroxide structure is obtained. -1 For example, the flow velocity can be 0.001 m·s. -1 0.005 m·s -1 0.01m·s -1 0.02 m·s -1 0.05 m·s -1 0.1 m·s -1 etc.; when the flow rate of the mixed solution or reaction solution is controlled to be 0.1–0.3 m·s. -1 A nano-flower-like copper oxide structure was obtained, wherein the flow rate was preferably controlled at 0.15–0.25 m·s. -1 .
[0017] Furthermore, the highest flow rate for forming the copper hydroxide coating was 0.1 m / s. -1 At this flow rate, copper hydroxide is generated below 10°C, while copper oxide is generated at higher temperatures.
[0018] Furthermore, in step (1), the cyclic reaction time is 30–60 min.
[0019] Furthermore, in step (2), the mass ratio of the amount of fresh strong alkali and persulfate mixed solution added to the amount of strong alkali and persulfate mixed solution added in step (1) is 0.8 to 3, for example, 0.8, 1, 1.5, 2, 2.5, 3, etc.; the cyclic reaction time is 30 to 60 min.
[0020] Furthermore, in step (3), the mass ratio of the amount of fresh strong alkali and persulfate mixed solution added to the amount of strong alkali and persulfate mixed solution added in step (1) is 0.8 to 3, for example, 0.8, 1, 1.5, 2, 2.5, 3, etc.; the cycle reaction time is 20 to 60 min.
[0021] Furthermore, in step (4), the drying conditions are: vacuum degree 0.09~0.1MPa, temperature 30~60℃, drying time 2~3h.
[0022] Furthermore, before performing step (1), the copper or copper alloy material can be pretreated. The pretreatment can be carried out using methods commonly used in the art, such as ultrasonically cleaning the copper or copper alloy material in concentrated hydrochloric acid, anhydrous ethanol, and deionized water for 20-50 minutes respectively, and then drying it with nitrogen gas; the concentration of the hydrochloric acid can be 1.5-3 mol·L. -1 .
[0023] According to a preferred embodiment of the present invention, the preparation method may include:
[0024] (1) At 5–60°C, the cleaned copper or copper alloy material is placed in a reactor, and a mixed solution of strong alkali and persulfate is pumped into the reactor using a metering pump. The flow rate of the mixed solution in the reactor is between 0.001 and 0.1 m·s. -1 The mixed solution is transported back to the storage tank through the reactor and circulated for 30-60 minutes. The reaction solution changes from a colorless solution to a light gray transparent solution.
[0025] (2) Use a metering pump to deliver a fresh mixture of strong alkali and persulfate to the storage tank. The ratio of the amount of fresh mixture added to the amount added for the first time is 0.8 to 3. Circulate the reaction for 30 to 60 minutes until the reaction solution becomes a light gray transparent solution.
[0026] (3) Use a metering pump to transfer a fresh mixture of strong alkali and persulfate to the storage tank. The amount of fresh mixture added should be the same as the amount added the first time. Circulate the reaction for 20–60 minutes.
[0027] (4) The reaction continues until the solution becomes a light gray transparent solution. Then the obtained sample is washed and dried to obtain a nanowire copper hydroxide structure.
[0028] In the above preparation method, the flow rate of the mixed solution in the reactor is controlled to be 0.1–0.3 m / s. -1 When done in this way, nano-flower-like copper oxide structures can be prepared.
[0029] A second objective of this invention is to provide a copper-based compound superhydrophilic material obtained by the aforementioned preparation method.
[0030] The copper-based superhydrophilic compound has a nanowire copper hydroxide structure, wherein the length of the nanowire copper hydroxide is 1–30 μm and the root diameter is 0.1–1 μm; or, the copper-based superhydrophilic compound has a nanoflower-like copper oxide structure, wherein the diameter of the nanoflower is 1–5 μm.
[0031] A third objective of this invention is to provide an apparatus for preparing controllable structured copper-based compound superhydrophilic materials, used for performing the above-described preparation method, including:
[0032] A reactor for reacting a mixed solution of strong alkali and persulfate with copper or copper alloy materials, having an inlet and an outlet;
[0033] The first storage tank has a first inlet and a second inlet at the top and an outlet at the bottom. The first inlet is connected to the outlet of the reactor through a pipeline, and the outlet of the first storage tank is connected to the inlet of the reactor through a pipeline.
[0034] The first metering pump is installed on the pipeline between the outlet of the first storage tank and the inlet of the reactor to ensure a stable liquid flow rate;
[0035] The second liquid storage tank has an inlet and an outlet, and its outlet is connected to the second inlet of the first liquid storage tank via a pipeline.
[0036] The second metering pump is installed on the pipeline between the first and second liquid storage tanks to ensure a stable liquid flow rate.
[0037] Furthermore, the reactor is preferably a tubular reactor such as a cylindrical reaction vessel, with a diameter of 1 mm to 300 mm and a length of 15 mm to 800 mm, and a filter screen is provided inside the reactor, such as at the outlet.
[0038] Preferably, the reactor has a liquid inlet and a temperature measuring port at the bottom, and a liquid outlet at the top.
[0039] Furthermore, the preparation apparatus may further include:
[0040] The first liquid flow controller is installed on the pipeline between the first metering pump and the reactor inlet;
[0041] The second liquid flow controller is installed on the pipeline between the second metering pump and the first liquid storage tank.
[0042] The nanowire-shaped copper hydroxide prepared in this invention is obtained through the co-oxidation of a strong base and persulfate. This invention regulates the structural morphology of copper hydroxide by controlling the circulation flow rate of the reaction solution containing different strong bases and persulfates, ultimately exploring a simple and rapid method for preparing nanowire-shaped copper hydroxide. This method can generate nanowire-shaped copper hydroxide on the surface of complex copper-based materials in a short time. Scanning electron microscopy reveals that the nanowires of the prepared nanowire-shaped copper hydroxide are uniformly distributed and possess excellent superhydrophilic properties, with a contact angle with water of approximately 0°. By adjusting the reaction process, nanoflower-like copper oxide can also be generated on the surface of copper-based materials. This invention also provides a simple, time-efficient, and easily scalable circulating reaction system for preparing controllable structured superhydrophilic copper-based compound materials.
[0043] The novel method of this invention produces copper hydroxide with nanowire structures, exhibiting uniform size with lengths of 1–30 μm and diameters of 0.1–1 μm. This nanowire-structured copper hydroxide demonstrates excellent hydrophilicity, with a water contact angle of approximately 0°, and can be developed for use as a substrate for structural functional materials.
[0044] The present invention has the following beneficial effects:
[0045] (1) This invention develops a strong base oxidation method for preparing copper hydroxide with nanowire-like or nanoflower-like structures. This method is simple, easy to operate, and has a short processing time. It can be applied to the processing of copper-based materials with complex geometric structures.
[0046] (2) The nanowire copper hydroxide prepared by the method developed in this invention has excellent hydrophilic properties and a contact angle of about 0°, and can be used as a substrate for structural functional materials.
[0047] (3) The nanowire structure prepared by the method developed in this invention increases the specific surface area of copper hydroxide and can be applied to chemical fields such as catalysis, reaction and distillation. Attached Figure Description
[0048] Figure 1 This is a schematic flowchart of the preparation method of the present invention;
[0049] Figure 1 Marker explanation:
[0050] 1-Second storage tank; 2-Second metering pump; 3-Second liquid flow controller; 4-First storage tank; 5-First metering pump; 6-First liquid flow controller; 7-Reactor.
[0051] Figure 1 In this process, copper or copper alloy material is added to reactor 7. A mixed solution of strong alkali and persulfate from the first storage tank 4 is delivered to reactor 7 using a first metering pump 5. The reaction is carried out at 5–60°C for a total reaction time of 80–180 minutes. During the reaction, fresh reaction solution is added twice. After 30–60 minutes, when the color of the reaction solution changes from colorless and transparent to bluish-gray and then to a light gray transparent solution, the first addition of fresh solution is performed. A second metering pump 2 delivers a fresh mixed solution of strong alkali and persulfate from the second storage tank 1 to storage tank 4. The mass ratio of the added fresh reaction solution to the original added reaction solution is 0.8–3. After 60–120 minutes, when the color of the reaction solution changes from colorless and transparent to bluish-gray and then to a light gray transparent solution, the second addition of fresh solution is performed, with the amount of fresh reaction solution added being the same as the first addition. Finally, the solution is removed, washed with water, and dried with nitrogen or under vacuum to obtain copper hydroxide with a nanowire structure or copper oxide with a nanoflower-like structure.
[0052] Figure 2 SEM image of the nanowire copper hydroxide prepared in Example 1;
[0053] Figure 3 A photograph of the static contact angle of nanowire copper hydroxide prepared in Example 1 with water in air;
[0054] Figure 4 SEM image of the nano-flower-like copper oxide prepared in Example 2;
[0055] Figure 5 SEM image of the nanowire copper hydroxide prepared in Example 3;
[0056] Figure 6 A photograph of the static contact angle of the nanowire copper hydroxide prepared in Example 3 with water in air;
[0057] Figure 7 SEM image of the nanowire copper hydroxide prepared in Example 4;
[0058] Figure 8 A photograph of the static contact angle of the nanowire copper hydroxide prepared in Example 4 with water in air;
[0059] Figure 9 SEM image of the nano-flower-like copper oxide prepared in Example 5;
[0060] Figure 10 SEM image of the nanowire copper hydroxide prepared in Example 6;
[0061] Figure 11 A photograph of the static contact angle of the nanowire copper hydroxide prepared in Example 6 with water in air;
[0062] Figure 12 SEM image of the nanowire copper hydroxide prepared in Example 7;
[0063] Figure 13 A photograph of the static contact angle of the nanowire copper hydroxide prepared in Example 7 with water in air;
[0064] Figure 14 SEM image of the copper sheet sample prepared for Comparative Example 1;
[0065] Figure 15 A photograph of the static contact angle of the copper sheet coating prepared for Comparative Example 1 with water in air. Detailed Implementation
[0066] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0067] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0068] Example 1
[0069] The specific steps for preparing nanowire-shaped copper hydroxide are as follows:
[0070] (1) Take the bulk packing material of the Sita ring (φ3x3mm, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and clean it ultrasonically for 15 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0071] (2) At 15℃, the tin-phosphorus bronze bulk packing treated in step (1) is loaded into the tubular reactor 7. The tubular reactor 7 is a tubular reactor with a length of 300mm and an inner diameter of 30mm. The two ends of the packing layer are wrapped with copper mesh. The first metering pump 5 delivers the mixed solution of sodium hydroxide and sodium persulfate in the first storage tank 4 to the reactor 7. The molar concentration ratio of sodium hydroxide to sodium persulfate in the mixed solution is 2:5, and the concentration of sodium hydroxide is 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. -1 The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.003 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0072] (3) After 40 minutes of cyclic reaction, the reaction solution changes from colorless to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of sodium hydroxide and sodium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0073] (4) After adding fresh reaction solution, react for 40 min, then add fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 30 min, take out the sample, wash it with pure water, and dry it for 2 h under a vacuum of 0.095 MPa and a temperature of 30 °C to obtain nanowire copper hydroxide.
[0074] After step (4), a copper sheet sample with nanowire-like copper hydroxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 2 ,Depend on Figure 2 It can be seen that the length of the copper hydroxide nanowires in this sample is 1–30 μm, and the root diameter is 0.1–0.8 μm. From Figure 3 It can be seen that nanowire-shaped copper hydroxide has excellent hydrophilic properties, with a contact angle of approximately 0°.
[0075] Example 2
[0076] The specific steps for preparing nano-flower-like copper oxide are as follows:
[0077] (1) Take the bulk packing material of the Sita ring (φ3x3mm, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and clean it ultrasonically for 25 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0078] (2) At 40℃, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 300mm and an inner diameter of 30mm. Both ends of the packing layer are wrapped with copper mesh. The first metering pump 5 delivers a mixed solution of sodium hydroxide and sodium persulfate from the first storage tank 4 to reactor 7. The molar ratio of sodium hydroxide to sodium persulfate in the mixed solution is 2:5, and the concentration of sodium hydroxide is 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. - 1. The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.2 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0079] (3) After 60 minutes of cyclic reaction, the reaction solution changes from colorless solution to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of sodium hydroxide and sodium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 0.8.
[0080] (4) After adding fresh reaction solution, react for 60 min, then add fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 20 min, take out the sample, wash it with pure water, and dry it for 2 h under a vacuum of 0.095 MPa and a temperature of 60 °C to obtain nano-flower-shaped copper oxide.
[0081] After step (4), a copper sheet sample with nano-flower-like copper oxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 4 ,Depend on Figure 4 It can be seen that the diameter of the nanoflowers in this sample is 1-5 μm.
[0082] Example 3
[0083] The specific steps for preparing nanowire-shaped copper hydroxide are as follows:
[0084] (1) Take the bulk packing material of the Sita ring (φ3x3mm, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and clean it ultrasonically for 25 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0085] (2) At 15℃, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 300mm and an inner diameter of 30mm. Both ends of the packing layer are wrapped with copper mesh. The first metering pump 5 delivers a mixed solution of potassium hydroxide and potassium persulfate from the first storage tank 4 to reactor 7. The molar concentration ratio of potassium hydroxide to potassium persulfate in the mixed solution is 25, the concentration of potassium hydroxide is 0.5mol·L-1, the concentration of potassium persulfate is 0.02mol·L-1, the molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.001m·s-1. The reaction solution is delivered to the first storage tank 4 through reactor 7.
[0086] (3) After 30 minutes of cyclic reaction, the reaction solution changes from colorless solution to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of potassium hydroxide and potassium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0087] (4) After adding fresh reaction solution, react for 40 min, then add fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 40 min, take out the sample, wash it with pure water, and dry it for 2 h under a vacuum of 0.095 MPa and a temperature of 30 °C to obtain nanowire copper hydroxide.
[0088] After step (4), a copper sheet sample with nanowire-like copper hydroxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 5 ,Depend on Figure 5 It can be seen that the length of the copper hydroxide nanowires in this sample is 1–30 μm, and the root diameter is 0.1–0.8 μm. From Figure 6 It can be seen that nanowire-shaped copper hydroxide has excellent hydrophilic properties, with a contact angle of approximately 0°.
[0089] Example 4
[0090] The specific steps for preparing nanowire-shaped copper hydroxide are as follows:
[0091] (1) Take the wire mesh corrugated structured filler (CY700, CY800, CY900, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and ultrasonically clean it for 15 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0092] (2) At 15℃, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 800 mm and an inner diameter of 300 mm. Both ends of the packing layer are wrapped with copper mesh. The first metering pump 5 delivers a mixed solution of sodium hydroxide and sodium persulfate from the first storage tank 4 to reactor 7. The molar ratio of sodium hydroxide to sodium persulfate in the mixed solution is 2:5, and the concentration of sodium hydroxide is 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. -1 The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.003 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0093] (3) After 40 minutes of cyclic reaction, the reaction solution changes from colorless to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of sodium hydroxide and sodium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0094] (4) After replenishing fresh reaction solution, react for 40 min, then replenish fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 20 min, then take out the sample, wash it with pure water, and dry it at a vacuum of 0.095 MPa and a temperature of 30 °C for 2 h to obtain nanowire copper hydroxide.
[0095] After step (4), a copper sheet sample with nanowire-like copper hydroxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 7 ,Depend on Figure 7 It can be seen that the length of the copper hydroxide nanowires in this sample is 1–30 μm, and the root diameter is 0.1–0.8 μm. From Figure 8 It can be seen that nanowire-shaped copper hydroxide has excellent hydrophilic properties, with a contact angle of approximately 0°.
[0096] Example 5
[0097] The specific steps for preparing nano-flower-like copper oxide are as follows:
[0098] (1) Take the wire mesh corrugated structured filler (CY700, CY800, CY900, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and ultrasonically clean it for 25 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0099] (2) At 40℃, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 800 mm and an inner diameter of 300 mm. The two ends of the packing layer are wrapped with copper mesh. The mixed solution of sodium hydroxide and sodium persulfate in the first storage tank 4 is transported to reactor 7 by the first metering pump 5. The molar concentration ratio of sodium hydroxide to sodium persulfate in the mixed solution is 2:5, and the concentration of sodium hydroxide is 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. -1 The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.2 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0100] (3) After 60 minutes of cyclic reaction, the reaction solution changes from colorless solution to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of sodium hydroxide and sodium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 0.8.
[0101] (4) After replenishing fresh reaction solution, react for 60 min, then replenish fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 20 min, then take out the sample, wash it with pure water, and dry it under vacuum of 0.095 MPa and temperature of 60℃ for 2 h to obtain nano-flower-shaped copper oxide.
[0102] After step (4), a copper sheet sample with nano-flower-like copper oxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 9 ,Depend on Figure 9 It can be seen that the diameter of the nanoflowers in this sample is 1-5 μm.
[0103] Example 6
[0104] The specific steps for preparing nanowire-shaped copper hydroxide are as follows:
[0105] (1) Take the wire mesh corrugated structured filler (CY700, CY800, CY900, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and ultrasonically clean it for 25 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0106] (2) At 15°C, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 800 mm and an inner diameter of 300 mm. Both ends of the packing layer are wrapped with copper mesh. A mixed solution of potassium hydroxide and potassium persulfate in the first storage tank 4 is transported to reactor 7 by the first metering pump 5. The molar ratio of potassium hydroxide to potassium persulfate in the mixed solution is 2:5, and the concentration of potassium hydroxide is 0.5 mol·L⁻¹. -1 The potassium persulfate concentration is 0.02 mol·L⁻¹. -1 The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in the reactor is 0.001 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0107] (3) After 30 minutes of cyclic reaction, the reaction solution changes from colorless solution to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of potassium hydroxide and potassium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0108] (4) After adding fresh reaction solution, react for 40 min, then add fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 40 min, take out the sample, wash it with pure water, and dry it for 2 h under a vacuum of 0.095 MPa and a temperature of 30 °C to obtain nanowire copper hydroxide.
[0109] After step (4), a copper sheet sample with nanowire-like copper hydroxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 10 ,Depend on Figure 10 It can be seen that the length of the copper hydroxide nanowires in this sample is 1–30 μm, and the root diameter is 0.1–0.8 μm. From Figure 11 It can be seen that nanowire-shaped copper hydroxide has excellent hydrophilic properties, with a contact angle of approximately 0°.
[0110] Example 7
[0111] The specific steps for preparing nanowire-shaped copper hydroxide are as follows:
[0112] (1) Take the bulk packing material of the Sita ring (φ3x3mm, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and clean it ultrasonically for 15 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0113] (2) At 15°C, the tin-phosphorus bronze bulk packing material treated in step (1) is loaded into reactor 7. Reactor 7 is a tubular reactor with a length of 300 mm and an inner diameter of 30 mm. Both ends of the packing layer are wrapped with copper mesh. The mixed solution of sodium hydroxide and sodium persulfate in the first storage tank 4 is transported to reactor 7 by the first metering pump 5. The molar concentration ratio of sodium hydroxide to sodium persulfate in the mixed solution is 2:5, and the concentration of sodium hydroxide is 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. -1 The molar ratio of copper to persulfate in the mixed solution is 150, and the flow rate of the mixed solution in reactor 7 is 0.03 m / s. -1 The reaction solution is transported from reactor 7 to the first storage tank 4.
[0114] (3) After 40 minutes of cyclic reaction, the reaction solution changes from colorless to light gray transparent solution. The second metering pump 2 delivers the fresh mixed solution of sodium hydroxide and sodium persulfate in the second storage tank 1 to the first storage tank 4. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0115] (4) After adding fresh reaction solution, react for 40 min, then add fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Continue to react for 30 min, take out the sample, wash it with pure water, and dry it for 2 h under a vacuum of 0.095 MPa and a temperature of 30 °C to obtain nanowire copper hydroxide.
[0116] After step (4), a copper sheet sample with nanowire-like copper hydroxide grown on its surface was obtained. The SEM image of this sample is shown below. Figure 12 ,Depend on Figure 12 It can be seen that the length of the copper hydroxide nanowires in this sample is 1–10 μm, and the root diameter is 0.2–1.0 μm. From Figure 13 It can be seen that nanowire-shaped copper hydroxide has excellent hydrophilic properties, with a contact angle of approximately 0°.
[0117] Comparative Example 1
[0118] The specific steps for preparing a hydrophilic coating using the static immersion method are as follows:
[0119] (1) Take the bulk packing material of the Sita ring (φ3x3mm, tin phosphor bronze with a copper purity of 97%) as the copper-based material, and clean it ultrasonically for 25 minutes in hydrochloric acid, anhydrous ethanol and deionized water respectively, and dry it with nitrogen for later use.
[0120] (2) At 15℃, the tin-phosphorus bronze bulk packing material treated in step (1) was placed into a beaker, and a mixed solution of sodium hydroxide and sodium persulfate was added. The molar ratio of copper to persulfate in the mixed solution was 150. The molar concentration ratio of sodium hydroxide to sodium persulfate in the mixed solution was 25, and the concentration of sodium hydroxide was 0.5 mol·L⁻¹. -1 The concentration of sodium persulfate is 0.02 mol·L⁻¹. -1 .
[0121] (3) After reacting for 30 minutes, add fresh reaction solution. The ratio of the amount of fresh reaction solution added to the mass of the original reaction solution is 1.5.
[0122] (4) After replenishing fresh reaction solution, let the reaction stand for 40 minutes. Then, replenish fresh reaction solution a second time. The amount of the second reaction solution added is the same as the amount added the first time. Let the reaction stand for another 40 minutes. Take out the sample, wash it with pure water, and dry it at a vacuum of 0.095 MPa and a temperature of 30°C for 2 hours to obtain a mixed coating of copper hydroxide and copper oxide with disordered morphology.
[0123] The copper sheet samples obtained after step (4) treatment are copper hydroxide and copper oxide. SEM images of these samples are shown below. Figure 14 .Depend on Figure 14 It can be seen that the morphology and structure of the coating on this sample are very chaotic, the coating distribution is uneven, and the length of the linear copper hydroxide can reach 80 μm. Figure 15 It can be seen that the coating with a disordered morphology has good hydrophilicity, with a contact angle of approximately 28.79°.
[0124] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a controllable structure copper-based compound superhydrophilic material, characterized in that, Includes the following steps: (1) A mixed solution of strong alkali and persulfate is passed through copper or copper alloy material to react, and the outflowing reaction solution is then returned to carry out a cyclic reaction; (2) When the reaction solution flowing out in step (1) changes from a colorless solution to a light gray transparent solution, add a fresh mixed solution of strong base and persulfate to the reaction solution, and then carry out the cyclic reaction; (3) Repeat step (2) 1 to 3 times; (4) When the reaction solution flowing out in step (3) becomes a light gray transparent solution, the obtained copper or copper alloy material is cleaned and dried to obtain a controllable structure copper-based compound superhydrophilic material with a nanowire copper hydroxide or nanoflower copper oxide structure on the surface. In steps (1) to (3): the strong base is an alkali metal hydroxide, and the concentration of the strong base is 0.5~3.0 mol•L. -1 The concentration of the persulfate is 0.025~0.15 mol•L. -1 The molar ratio of the strong base to the persulfate in the mixed solution is (12~60):1; the reaction is carried out at 5~60℃; and the flow rates of the mixed solution and the reaction solution are controlled at 0.001~0.1 m•s. -1 When the flow rates of the mixed solution and the reaction solution are controlled at 0.1~0.3 m•s, a nanowire-like copper hydroxide structure is obtained. -1 At that time, a nano-flower-like copper oxide structure was obtained; The highest flow rate for forming the copper hydroxide coating was 0.1 m·s. -1 At this flow rate, copper hydroxide is generated below 10°C, while copper oxide is generated at higher temperatures.
2. The preparation method according to claim 1, characterized in that, In steps (1) to (3): the strong base is selected from at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide, and the persulfate is selected from at least one of ammonium persulfate, sodium persulfate and potassium persulfate.
3. The preparation method according to claim 1, characterized in that, In steps (1) to (3): the molar ratio of the strong base to the persulfate in the mixed solution of the strong base and persulfate is (15~25):
1.
4. The preparation method according to claim 1, characterized in that... In step (1): The copper or copper alloy material is either a bulk packing or a structured packing. The bulk packing is at least one of Sita rings, Pall rings, Raschig rings, rectangular saddle rings, and stepped rings. The structured packing is at least one of wire mesh corrugated packing, perforated plate corrugated packing, plate mesh corrugated packing, and perforated plate corrugated packing. The copper purity of the copper or copper alloy material is 95-99.99%, and the cycle reaction time is 30-60 min.
5. The preparation method according to claim 1, characterized in that... In step (2): The mass ratio of the amount of fresh strong alkali and persulfate mixed solution added to the amount of strong alkali and persulfate mixed solution added in step (1) is 0.8~3, and the cyclic reaction time is 30~60min.
6. The preparation method according to claim 1, characterized in that... In step (3): The mass ratio of the amount of fresh strong alkali and persulfate mixed solution added to the amount of strong alkali and persulfate mixed solution added in step (1) is 0.8~3, and the cyclic reaction time is 20~60min.
7. A copper-based compound superhydrophilic material obtained by the preparation method according to any one of claims 1 to 6.
8. The copper-based compound superhydrophilic material according to claim 7, characterized in that, The copper-based compound superhydrophilic material has a nanowire copper hydroxide structure or a nanoflower copper oxide structure on its surface; the length of the nanowire copper hydroxide is 1~30 µm and the root diameter is 0.1~1 µm; the diameter of the nanoflower is 1~5 µm.
Citation Information
Patent Citations
Sponge substrate chemical nickeling device
CN105568268A
Preparation method of copper oxide with nano flower-like structure
CN112897567A